“From the farm to the plate”: agro-biodiversity valorization as a tool for promoting a sustainable diet - Renna, Massimiliano (Progress in Nutrition, 2015)
In the early 1980s Gussow and Clancy (1) described the notion of “sustainable diets” as …recommended diets that are healthier for the environment as well as for the consumers... This concept, borrowed from “sustainable agriculture”, allowed to promote several activities with the aim to minimize the waste of natural resources and address to food production toward local and seasonal consumption. However, the concept of a sustainable diet is a complex issue and there are still many gaps in our understanding of what a sustainable diet might comprise (2). [...]